Impact of Family Counselling on the Psychological Well-Being of Cancer Patients attending Oncology Clinics in Meru County - Magambo, Margaret Ndiah; Wachira, Rebecca; Gichohi, Paul Maku (International Journal of Professional Practice, 2024)
Cancer patients face significant physical, emotional, and psychological challenges that impact their overall health, indicating unmet need for psychosocial support. Lack of psychological support worsens the well-being of cancer parents, and complicates medical treatment and recovery. Many oncology clinics lack sufficient mechanisms for engaging family members in helping patients navigate psychosocial challenges. Unfortunately, this undermines efforts by the Ministry of Health, which allocates resources and deploys qualified personnel for cancer management. In seeking solutions to this situation, this study aimed to evaluate the impact of family counselling on the psychological well-being of cancer patients attending oncology clinics in Meru County, Kenya. The study was anchored on social cognitive theory and utilized a convergent survey research design. The target population comprised 2580 cancer patients, 2580 caregivers and 53 clinicians; out of which 335 cancer patients, 40 caregivers and 6 clinicians were sampled. Questionnaires, interviews, and focus group discussions were used to collect data. The study adopted systematic, random and purposive sampling techniques in selecting subjects. Data collection tools were questionnaires, interviews and focus group discussions. Reliability and validity were established accordingly. Both descriptive and inferential statistics, and thematic analysis were used to analyze data. Findings indicated that family counselling significantly reduced stigma, increased cancer knowledge and understanding, and consequently improved the psychological well-being of patients. The study recommended integration of family counselling into oncology clinics owing to its value in addressing family dynamics, enhancing decision-making, harmony, emotional, social, nutritional, financial and spiritual wellbeing, as well as other dimensions linked to cancer patient welfare. Clinicians, psychologists, and caregivers should prioritize a holistic approach in family counselling, encompassing comprehensive family involvement, continuous family members empowerment, coordinated decision-making, and family-tailored counselling sessions. Policies should prioritize adequate resources, cultural competence training, integrated family-centred services, and inter-professional collaborations to address challenges undermining cancer patients’ psychological well-being.